Main errors in the pre-analytical phase of laboratory tests: an integrative literature review (Research, Society and Development, 2021)
In a panoramic view of the diagnostic services provided by the laboratories, it is clear that there is a practical relationship in helping the health professional in order to elucidate the therapeutic treatment applied to the patient, being necessary to comply with the applicable legislation to standardize and provide control plausible quality of the results obtained. The pre-analytical phase is the most important in the testing process and involves variables that are not under the laboratory's control. Great care needs to be taken to look deeply into this step of the analysis and keep a record of the errors that arise in it. This research aims to carry out a study of the main errors of the pre-analytical phase, emphasizing the collection of materials and transport, where the most common errors are found, evident in the process in which it involves mostly manual work. Thus, it can be concluded that the practice of keeping a record of errors at all stages of the analysis and then developing corrective strategies for their prevention can exponentially free a laboratory of such errors.